(untitled) (Conference on English Language Teaching, 2023)
The adoption of technology in the learning process has been extensively researched, focusing on students’ level of technological acceptance. This descriptive research study aimed to determine the level of technological acceptance among college students. A standardized questionnaire was administered to randomly selected respondents. Statistical analyses, including frequency, mean, Mann-Whitney U Test, and Kruskal-Wallis Test, were conducted. The results indicated that there were no significant differences in technology acceptance based on gender and age. However, significant differences were observed based on year level and program, with third-year students and those in the DTE program exhibiting the highest level of acceptance. Overall, respondents demonstrated a moderately high level of technology acceptance, with "Intention to Use" obtaining the lowest mean score. To enhance students’ understanding of technology’s significance and encourage continued technological advancement, especially during the pandemic, the researchers recommend conducting a seminar titled "Blended Learning: The New Normal and Emerging Technologies.".